Recent trends in technical education in Latin America - Jacinto, CLaudia (Paris UNESCO, International Institute for Educational Planning, 2010)
"This book examines recent transformations with regards to the links between academic secondary education (ASE), technical and vocational education and training (TVET), and job preparation skills, in the Latin America region. It analyses changes in approaches, obstacles and advances, and major challenges, and reviews some promising strategies."--www.iiep.unesco.org
The background of the relations between general secondary and technical education and employment in Latin America : eight points / by Claudia Jacinto -- Trends in technical and vocational education and training in Latin America / by Irma Briasco -- Preparing for work in general secondary education : recent debates and approaches in Latin America / by Claudia Jacinto -- Approaches and strategies for the vocational training of unemployed youth in Latin America : has anything changed in recent years? / by Claudia Jacinto -- The development of systems of competency-based training and certification in Latin America : a general review / by Fernando Vargas Zuniga.
Keywords: Technical education -- Latin America; Vocational education -- Latin America; Education, Secondary -- Latin America